Pemikiran Teodisi Ibn Arabi Tentang Keburukan - Yoshy Hendra Hardiyan Syah (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2022)
This article discusses Ibn Arabi's theodic thoughts on evil in studying, understanding, and exploring more deeply the case of the Covid-19 virus as the implications of evil. Theodicy is a philosophical problem based on a number of arguments and is accompanied by the arguments of philosophical thought so that it can explain and solve a case proportionally and theodicy is a theme that is often the subject of debate, namely more questions about justice over God's omnipotence. In this research, it is sourced from the literature or literature review as research material and a descriptive study and analysis of Ibn Arabi's theodic thought about evil. Ibn Arabi thoroughly discusses the theodic discussion of evil in his book entitled Futuhat al-Makkiyah and Fushush al-Hikam. The problem of good and bad seems to be consistent with the Wahdat al-Wujud theory, he says in the book Futuhat al-Makkiyah that